ANALISA LAJU KOROSI PADA SISTEM PEMIPAAN BAWAH TANAH PT. CHEVRON PACIFIC INDONESIA - Syawaldi - (Universitas Pasir Pengaraian, 2013)
Corrosion is a problem that always happens to the equipment of oil and gas production. Pipe production is one piece of equipment that will not be separated from the process of corrosion. Long Range Ultrasonic Testing is one method that can be used to detect the onset of corrosion in the production pipeline. The method makes use of ultrasonic waves as a medium in the complete evaluation by teletest unit as system settings. In the test series in the field of production pipe Arzon # 89 the corrosion rate will be obtained when the magnitude of the reduction is calculated first pipe wall thickness (wall loss) of yield teletest data reporting system.